Pengaruh Sales Growth Dan Likuiditas Terhadap Nilai Perusahaan Dengan Profitabilitas Sebagai Variabel Intervening Pada Perusahaan Properti Dan Real Estate Yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2019-2022 - Novita Parasian Manurung; Diana Hasyim (PPIMAN Pusat Publikasi Ilmu Manajemen, 2024)
The purpose of this study is to determine the effect of sales growth and liquidity on firm value with profitability as an intervening variable. The research population consists of 91 companies listed on the Indonesia Stock Exchange (IDX) from 2019-2022. The sampling technique used is purposive sampling, resulting in a sample of 47 companies for this study. The analysis technique employed is panel data analysis using Eviews12 software. The results of the research indicate that: 1) Sales growth has a positive and significant effect on profitability. 2) Sales growth has a negative and significant effect on firm value. 3) Liquidity has a positive and significant effect on profitability. 4) Liquidity has a negative and significant effect on firm value. 5) Profitability has a positive and significant effect on firm value, and 6) Profitability can mediate the effect of sales growth and liquidity on firm value.